Functionalizing DNA nanostructures for therapeutic applications. (19th May 2021) - Henry, Skylar J. W.; Stephanopoulos, Nicholas
Abstract: Recent advances in nanotechnology have enabled rapid progress in many areas of biomedical research, including drug delivery, targeted therapies, imaging, and sensing. The emerging field of DNA nanotechnology, in which oligonucleotides are designed to self‐assemble into programmable 2D and 3D nanostructures, offers great promise for further advancements in biomedicine. DNA nanostructures present highly addressable and functionally diverse platforms for biological applications due to their ease of construction, controllable architecture and size/shape, and multiple avenues for chemical modification. Both supramolecular and covalent modification with small molecules and polymers have been shown to expand or enhance the functions of DNA nanostructures in biological contexts. These alterations include the addition of small molecule, protein, or nucleic acid moieties that enable structural stability under physiological conditions, more efficient cellular uptake and targeting, delivery of various molecular cargos, stimulus‐responsive behaviors, or modulation of a host immune response. Herein, various types of DNA nanostructure modifications and their functional consequences are examined, followed by a brief discussion of the future opportunities for functionalized DNA nanostructures as well as the barriers that must be overcome before their translational use. This article is categorized under: Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Therapeutic Approaches and Drug Discovery > Emerging Technologies Biology‐Inspired Nanomaterials > Nucleic Acid‐Based Structures Abstract : This Review examines recent advances in DNA nanotechnology that expand the function of these nanostructures in biological contexts. These functional modifications include stabilization under physiological conditions, efficient cellular uptake and targeting, delivery of therapeutic cargos, stimulus‐responsive behaviors, and immune modulation.